2012
DOI: 10.4103/0970-9185.92449
|View full text |Cite
|
Sign up to set email alerts
|

A comparative randomized study of paravertebral block versus wound infiltration of bupivacaine in modified radical mastectomy

Abstract: Background:Paravertebral block (PVB) has the potential to offer long-lasting pain relief because it can uniquely eliminate cortical responses to thoracic dermatomal stimulation. Benefits include a reduction in postoperative nausea and vomiting (PONV), prolonged postoperative pain relief, and potential for ambulatory discharge.Aims:To compare PVB with local infiltration for postoperative analgesia following modified radical mastectomy (MRM).Methods:Forty patients undergoing MRM with axillary dissection were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…8 Our results of optimal pain control with TPVB are in agreement with the findings of previous studies which showed that TPVB was an effective option for postoperative analgesia and its use obviated the need for epidural block as well as systemic opioids thereby avoiding side effects associated with these therapeutic modalities. 5,8,14,15 TPVB patients reported less pain than their no-block counterparts; there was significant difference in the VRS until 24 h postoperatively. The pain relief was so profound that no patient in the TPVB group required opioid and non-opioid analgesic within 24 h. This observation differs from results of single-shot multi-level TPVBs in which significant differences in pain scores, opioid analgesic consumption lasted 6-8 h. 16,17 Our explanation for this difference is that in the lamina TPVB technique, the catheter that is tunneled into the TPVS allows the injection of a higher LA volume which engenders a better cranio-caudal spread than the multi-level classical approach.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…8 Our results of optimal pain control with TPVB are in agreement with the findings of previous studies which showed that TPVB was an effective option for postoperative analgesia and its use obviated the need for epidural block as well as systemic opioids thereby avoiding side effects associated with these therapeutic modalities. 5,8,14,15 TPVB patients reported less pain than their no-block counterparts; there was significant difference in the VRS until 24 h postoperatively. The pain relief was so profound that no patient in the TPVB group required opioid and non-opioid analgesic within 24 h. This observation differs from results of single-shot multi-level TPVBs in which significant differences in pain scores, opioid analgesic consumption lasted 6-8 h. 16,17 Our explanation for this difference is that in the lamina TPVB technique, the catheter that is tunneled into the TPVS allows the injection of a higher LA volume which engenders a better cranio-caudal spread than the multi-level classical approach.…”
Section: Discussionmentioning
confidence: 94%
“…Thoracic paravertebral block (TPVB) has been shown to provide prolonged postoperative pain relief for unilateral breast operations. 4,5 Consequently, our team began performing single-shot TPVB using the new lamina approach as an adjunct to general anaesthesia (GA) for major breast surgery. 6 To the best of our knowledge, no study has investigated the effectiveness of single-shot lamina TPVB.…”
Section: Introductionmentioning
confidence: 99%
“…[1] that presents the critical and innovative perspective of peri-anesthesia management. It has been my subjective understanding based on my observations that the surgical handling and stimulation of the eye globe, breasts and testicles elicit nauseating responses in the patients.…”
mentioning
confidence: 99%
“…Additionally, these responses cannot be blocked with postoperative regional blocks as the physiological changes and reflexive mechanisms have been initiated to varying degrees intraoperatively that will present as PONV in pre-emptively untreated patients. [1] As wound infiltrations and surgical field/incision local anesthetic blocks can only be accomplished at the end of the surgeries, the clinically significant pre-emptive anti-emesis can only be achieved with pre-incision paravertebral/epidural blocks for mastectomies and pre-incision caudal/epidural/spinal/spermatic cord blocks for adult or pediatric testicular surgeries; however, peri-bulbar/retro-bulbar blocks for eye-muscle surgeries may have a concern for counter-productive surgical results in terms of the inadequate corrections of heterotropia. In summary, the observations of Bansal et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation